Efficacy of digital CBT for insomnia to reduce depression across demographic groups: a randomized trial. Issue 3 (24th May 2018) - Cheng, Philip; Luik, Annemarie I.; Fellman-Couture, Cynthia; Peterson, Edward; Joseph, Christine L.M.; Tallent, Gabriel; Tran, Kieulinh Michelle; Ahmedani, Brian K.; Roehrs, Timothy; Roth, Thomas; Drake, Christopher L.
Abstract: Background: Insomnia and depression are highly comorbid and mutually exacerbate clinical trajectories and outcomes. Cognitive behavioral therapy for insomnia (CBT-I) effectively reduces both insomnia and depression severity, and can be delivered digitally. This could substantially increase the accessibility to CBT-I, which could reduce the health disparities related to insomnia; however, the efficacy of digital CBT-I ( d CBT-I) across a range of demographic groups has not yet been adequately examined. This randomized placebo-controlled trial examined the efficacy of d CBT-I in reducing both insomnia and depression across a wide range of demographic groups. Methods: Of 1358 individuals with insomnia randomized, a final sample of 358 were retained in the d CBT-I condition and 300 in the online sleep education condition. Severity of insomnia and depression was examined as a dependent variable. Race, socioeconomic status (SES; household income and education), gender, and age were also tested as independent moderators of treatment effects. Results: The d CBT-I condition yielded greater reductions in both insomnia and depression severity than sleep education, with significantly higher rates of remission following treatment. Demographic variables (i.e. income, race, sex, age, education) were not significant moderators of the treatment effects, suggesting that d CBT-I is comparably efficacious across a wide range of demographic groups. Furthermore, while differences in attrition were found based on SES, attrition did not differ between white and black participants. Conclusions: Results provide evidence that the wide dissemination of d CBT-I may effectively target both insomnia and comorbid depression across a wide spectrum of the population.